An electrodeposition metal layers method for magnetic powders and warm-pressing preparation of Nd–Fe–B/Sn-bonded magnets. Issue 3 (1st February 2016) - Zheng, Jingwu; Cheng, Xiaotian; Chen, Haibo; Qiao, Liang; Lin, Min; Jiang, Liqiang; Che, Shenglei
Abstract: The method of magnetic stirring in fluid-bed galvanic deposits was used for cladding low-melting-point metallic tins onto the surface of rapid quenching Nd–Fe–B magnetic powders. This form of bonding was also used to make Nd–Fe–B/Sn composite magnets by warm pressing at 300 °C. The tin-plating layers of the Nd–Fe–B magnetic particles were observed by scanning electron microscope (SEM). The magnetic properties of the coated and uncoated powders were examined by vibrating sample magnetometer (VSM), respectively. Furthermore, both the compressive strength and magnetic properties of Sn-coated Nd–Fe–B/Sn-bonded magnets were measured. The results indicate that not only the tin plated and magnetic powders were bonded closely, but also the content of tin-plated layers can be controlled by the electrical current. The (BH)max and Br value of magnetic powders decrease with the increasing content of plated tin. An increase in the tin-plated content results in an elevation in magnetic properties of composite magnets by warm-pressing preparation. The composite magnets exhibit excellent integrated magnetic property when the content of Sn was 5.079 wt.%, at (BH)max  = 113.7 kJ m −3, Br  = 0.821 T, Hcj  = 732.6 kA m −1 . The results indicate that the required electrodeposited tin is less than 5 wt.% achieving the same magnetic properties and compressive strength which demands 10 wt.% tin in mechanical mixing method.